2006
DOI: 10.1108/10444060610742344
|View full text |Cite
|
Sign up to set email alerts
|

Conflict resolution styles between co‐workers in US and Mexican cultures

Abstract: Purpose -The purpose of this study is to investigate how national culture and proximity to national borders can influence the conflict styles that co-workers use between themselves. Design/methodology/approach -In this experiment, samples were drawn from regions near the US Mexican border further north in the USA and further South in Mexico. Total n ¼ 549. Participants were presented with different conflict styles of co-workers and asked how they would respond. A new measure of national origin was developed an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 35 publications
0
16
0
3
Order By: Relevance
“…Likewise, research has shown that individual conflict styles impact conflict partners' behavior (cf. Posthuma et al, 2006). Further research opportunities exist in linking individual conflict styles with team processes of debate and decision comprehensiveness.…”
Section: Limitations and Further Researchmentioning
confidence: 96%
See 1 more Smart Citation
“…Likewise, research has shown that individual conflict styles impact conflict partners' behavior (cf. Posthuma et al, 2006). Further research opportunities exist in linking individual conflict styles with team processes of debate and decision comprehensiveness.…”
Section: Limitations and Further Researchmentioning
confidence: 96%
“…Collaborating and accommodating styles might foster open debate and integrating decisions, while contending and avoiding styles might hinder these team processes. Furthermore, the notion of cultural differences has been frequently stressed in conflict management research (Chen et al, 2012;Posthuma et al, 2006). Lu et al (2011) argue that cultural context and the organizational consequences of conflict have to be taken into consideration.…”
Section: Limitations and Further Researchmentioning
confidence: 99%
“…In particular, we examine the behavioral outcomes of how consumers frame conflict with service providers. Such research is important because understanding how people deal with conflict has been demonstrated to be essential to developing effective management strategies in other business contexts (e.g., Adair et al 2001;Barclay 1991;Friedman et al 2000;Koza and Dant 2007;Pinkley and Northcraft 1994;Posthuma et al 2006;Purohit and Simmers 2006;Rahim 1986). To address our research questions, we adopt a grounded theory approach.…”
Section: Introductionmentioning
confidence: 98%
“…One potential explanation for the mixed findings might be that previous studies have often failed to consider the culture-specific pattern of emotional intelligence (Gunkel, Schlä gel, & Engle, 2014;Miller, 1997;Shao, Doucet, & Caruso, 2014). While previous studies have shown that preferences for conflict handling styles vary substantially across countries (e.g., Doucet, Jehn, Weldon, Chen, & Wang, 2009;Gabrielidis, Stephan, Ybarra, Pearson, & Villareal, 1997;Kim, Wang, Kondo, & Kim, 2007;Posthuma, White, Dworkin, Yá nez, & Swift, 2006;Ting-Toomey et al, 1991), only a small number of studies (e.g., Kaushal & Kwantes, 2006;Komarraju, Dollinger, & Lovell, 2008;Morris et al, 1998) has analyzed the underlying reasons for these differences. Prior research suggests that differences in individuals' orientation toward different cultural value dimensions (i.e., the set of aspects that characterize a society according to its apparent place within the continuum of patterns described by the respective aspect) may be one promising explanation for cross-country differences in individual preferences for conflict handling styles (e.g., Holt & DeVore, 2005;Komarraju et al, 2008).…”
mentioning
confidence: 99%